2005
DOI: 10.1071/bt04016
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific variation in carbohydrate reserves and sprouting ability in Eucalyptus obliqua seedlings

Abstract: Seedlings of 13 provenances of Eucalyptus obliqua L’Hér. grown under favourable moisture and nutrient conditions in a glasshouse for 9 months showed significant differences in seedling height, lignotuber size and carbohydrate reserve pools in roots and lignotubers. Lignotuber size was strongly and inversely correlated with mean annual rainfall of the source provenance, and larger E. obliqua lignotubers had higher concentrations and pools of carbohydrate reserves than smaller lignotubers. When seedling stems we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
2
23
0
4
Order By: Relevance
“…Lignotubers occur in many taxa and are belowground swellings at the base of the stem harbouring carbohydrate stores and dormant buds. Shoots develop from lignotubers after severe damage to the main plant stem from, for example, drought, fire, or herbivory (Borzak, Potts, Barry, Pinkard, & O'Reilly‐Wapstra, ; Lloret, Verdu, Flores‐Hernandez, & Valiente‐Banuet, ; Paula & Pausas, ; Walters, Bell, & Read, ). Quantitative genetic studies have shown that lignotuber size is highly heritable (Whittock et al, ) and in some species is likely to be an important adaptation for survival in drier environments (Gauli, Vaillancourt, Bailey, Steane, & Potts, ; Walters, Bell, & Read, ; Whittock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lignotubers occur in many taxa and are belowground swellings at the base of the stem harbouring carbohydrate stores and dormant buds. Shoots develop from lignotubers after severe damage to the main plant stem from, for example, drought, fire, or herbivory (Borzak, Potts, Barry, Pinkard, & O'Reilly‐Wapstra, ; Lloret, Verdu, Flores‐Hernandez, & Valiente‐Banuet, ; Paula & Pausas, ; Walters, Bell, & Read, ). Quantitative genetic studies have shown that lignotuber size is highly heritable (Whittock et al, ) and in some species is likely to be an important adaptation for survival in drier environments (Gauli, Vaillancourt, Bailey, Steane, & Potts, ; Walters, Bell, & Read, ; Whittock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A maior taxa inicial de crescimento da brotação, em comparação à de plantas estabelecidas a partir de mudas, se deve, principalmente, à presença de um sistema radicular já estabelecido, o que facilita a absorção de água e nutrientes e o uso de reservas orgânicas e inorgânicas, presentes na cepa ou nas raízes (Blake, 1983;Reis & Kimmins, 1986;Teixeira et al, 2002;Kabeya & Sakai, 2005;Walters et al, 2005). Reis & Kimmins (1986) observaram que, após decepa de plantas jovens de eucalipto que cresciam em vasos, o sistema radicular contribuiu com 75% do fósforo requerido para o crescimento dos brotos, em solo relativamente fértil, e 100%, em solo pouco fértil, 1,5 mês após decepa das plantas.…”
Section: Introductionunclassified
“…Sims et al (2001) reported that the mean coppice height and biomass of Eucalyptus, Salix, Populus and Acacia were significantly higher than that of the first rotation, when harvested at the age of 3 years. The fast coppice growth in younger ages is a result of organic and inorganic reserves utilization from the stump or the root system as well as water and nutrient absorption by the established root system (Reis and Kimmins 1986;Oliveira et al 1994;Teixeira et al 2002;Kabeya and Sakai 2005;Luostarinen and Kauppi 2005;Walters et al 2005;Drake et al 2009Drake et al , 2012.…”
Section: New Forestsmentioning
confidence: 97%